Cell-Surface Displayed Expression of Trehalose Synthase from Pseudomonas putida ATCC 47054 in Pichia Pastoris Using Pir1p as an Anchor Protein - Yang, Shaojie; Lv, Xin; Wang, Xihui; Wang, Junqing; Wang, Ruiming; Wang, Tengfei (Frontiers in Microbiology, 2017)
Yeast cell-surface display technologies have been widely applied in the fields of food, medicine, and feed enzyme production, including lipase, α-amylase, and endoglucanase. In this study, a treSgene was fused with the yeast cell-surface anchor protein genePir1pby overlap PCR, the Pir1p-treS fusion gene was ligated intopPICZαA and pGAPZαA and transformed intop.pastorisGS115 to obtain recombinant yeast strains that displays trehalose synthase(TreS) on its cell surface as an efficient and recyclable whole-cell biocatalyst. Firstly, the enhanced green fluorescence protein gene (egfp) was used as the reporter protein to fusion the Pir1p gene and treS gene to construct the recombinant plasmids containing treS-egfg-Pir1p fusion gene, and electrotransformed into p.pastorisGS115 to analyze the surface display characteristics of fusion gene by Western blot, fluorescence microscopy and flow cytometry. The analysis shown that the treS-egfg-Pir1pfusion protein can successfully display on the surface of yeast cell, and the expression level increased with the extension of fermentation time. Reasoning from this result, the Pir1p-treS fusion gene can be well displayed on the cell surface. Secondly, in order to obtain surface active cells with high enzyme activity, the enzymatic properties of TreS displayed on the cell surface was analyzed, and the fermentation process of recombinant P.patoris GS115 containing pPICZαA-Pir1p-treS and pGAPZαA-Pir1p-treS was studied, respectively. The cell surface display TreS was stable over a broadrange of temperatures (10–45 °C) and pH (6.0–8.5). The activity ofTreSdisplayed on cell surfacerespectively reached 1,108 Ug-1under PAOX1 control for 150 h, and 1,109 Ug-1 under PGAP control for 75h in a 5 L fermenter, respectively.Lastly, the cell-surface displayed TreS was used to product trehalose using high maltse syrup as substrate at pH 8.0 and 15 ℃. The surface display TreS cells can be recycly used for three times and the weight conversion rate of trehalose was more than 60%. This paper revealed that the TreScan displayed on the P. pastoris cell surface and still had a higher catalytic activity after used recycly three times, which was suitable for industrial application, especially the preparation of pharmaceutical grade trehalose products.